Pulse-field electrophoresis indicates full-length Mycoplasma chromosomes range widely in size. - Neimark, H C (1990)
Full-size linear chromosomes were prepared from mycoplasmas by using gamma-irradiation to introduce one (on average) double-strand break in their circular chromosomes. Chromosome sizes were estimated by pulsed-field gel electrophoresis (PFGE) from the mobilities of these full-length molecules relative to DNA size references. Sizes estimated for Ureaplasma urealyticum T960 and 16 Mycoplasma species ranged from 684 kbp (M. hominis) to 1315 kbp (M. iowae). Using this sample, we found no correlation between the mobility of the full-size linear chromosomes and their G + C content. Sizes for A. laidlawii and A. hippikon were within the range expected from renaturation kinetics. PFGE size estimates are in good agreement with sizes determined by other methods, including electron microscopy, an ordered clone library, and summation of restriction fragments. Our estimates also agree with those from renaturation kinetics for both the largest and some of the smallest chromosomes, but in the intermediate size range, renaturation kinetics consistently provides lower values than PFGE or electron microscopy. Our PFGE estimates show that mycoplasma chromosomes span a continual range of sizes, with several intermediate values falling between the previously recognized large and small chromosome size clusters.